Influence of energy structure, environmental regulations and human capital on ecological sustainability in EKC framework; evidence from MINT countries - Saqib, Najia; Duran, Ivan A.; Sharif, Ilma (Frontiers in Environmental Science, 2022)
Heterogeneous anthropogenic and insufficient development strategies have caused an international compromise between sustainable growth and environmental deterioration. Environmental concerns have necessitated rules and human capital to protect the global ecosystem. Literature is ambiguous on the usefulness of environmental rules in reducing environmental deterioration. This study examines the impact of environmental regulations and education as a proxy for human capital in Mexico, Indonesia, Nigeria, and Turkey (MINT) countries' ecological footprints between 1990 and 2020. The econometric research shows that present environmental restrictions in MINT countries are unsuccessful at reducing their ecological footprints. Energy consumption and trade-openness also increase ecological footprints. The MINT countries panel also confirms the Environmental Kuznets Curve idea. The country-specific findings show that energy use silently harmed the environment in MINT nations, whereas environmental legislation, economic growth, and trade-openness had diverse effects. These findings suggest that in order for MINT nations to achieve environmental sustainability, they should strengthen and enforce environmental regulations; adopt policies that promote sustainable economic growth; reduce their reliance on fossil-fuels; improve quality education and awareness; and actively engage in sustainable trading activities.